MODELING IMPACT OF CLIMATE CHANGE IN HYDROPOWER PROJECTS’ FEASIBILITY VALUATION - SUAREZ, Ronny Araya (Journal of Environmental Management and Tourism; Vol 3 No 2 (2012): JEMT Volume III Issue 2(6) Winter 2012, 2016)
In this paper a case study is presented to propose an alternative mechanism to include the impact of climate change into the hydropower projects’ feasibility valuation. We start from independent engineer historical energy generation simulations, therefore applying mixing unconditional disturbance and extreme value theory, a new path that satisfy a return level specification is created. New path is used to analyze the effect of extreme events on the internal rate of return of the project. This mechanism could be used also to execute a simple sensitivity test that it’s done with an educated guess.
Keywords: extreme value theory, generalized Pareto distribution, return level, mixing unconditional disturbances, climate change, and stress testing